Contribution of sell-side equity analyst reports to client’s return and stock price efficiency: Indonesia stock market evidence - Ekaputra, Irwan Adi; Susilawati, C. Erna; Utama, Cynthia Afriani (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present study investigates whether equity analyst reports benefit clients and improve stock price efficiency. Companyfocus reports issued and documented by six brokerage companies in Indonesia are collected and the analysis focuses on the revisions of stock recommendations (upgrade, downgrade, or reiteration); earnings forecasts; and price targets.First, the results show that analyst reports contribute to client’s returns. Upgrade revisions, downgrade revisions and price target revisions significantly influence clients’ abnormal returns. However, clients do not seem to take into account earnings forecast revisions. Second, the finding reveal that analyst reports contribute to stock price efficiency. Upgrade revisions and price target revisions improve price efficiency. However, earnings forecast revisions and downgrade revisions do not appear to improve price efficiency. Third, the results indicate that price efficiency improvement tends to reduce non-client (market) abnormal returns, which corroborates the second finding.